A review of practitioner-led evaluation of teacher professional development - McChesney, K.; Aldridge, Jill (2018)
The central role of teacher professional development in educational improvement is well-documented, and the investments of time and money into teacher professional development across the globe are immense. Given, however, that the quality of professional development has been shown to vary considerably, meaningful evaluation of professional development activities is critical and has been widely advocated by both researchers and education system leaders. Whereas past reviews have examined the nature and quality of researcher-led evaluations of professional development, the present review focuses on the nature and quality of practitioner-led evaluations. Using current theoretical recommendations for effective evaluation as benchmarks, the review examines the degree to which these recommendations are reflected in routine school-based evaluation of professional development, finding that a significant gap persists between theory and practice. The review also identifies practical and psychological factors that restrict further improvement in practitioner-led evaluation and proposes ways in which researchers, practitioners and policymakers could each contribute to future improvement in practitioner-led evaluation of professional development. Given that much teacher professional development occurs within school settings and/or is managed by school staff, improving the quality of routine practitioner-led evaluation of that professional development is a potentially powerful driver for positive change.